2003
DOI: 10.1002/ejoc.200300119
|View full text |Cite
|
Sign up to set email alerts
|

[2+2+2] Cocyclotrimerization with Ferrocenylalkynes

Abstract: Cocyclotrimerization of ferrocenylalkynes FcC≡CR (R = H and CH2OH) with α,ψ‐diynes X(CH2C≡CH)2, where X = O, C(CO2Et), C(CN)(CO2Et), C(COMe)2, and C(COMe)(CO2Et), to give functionalised ferrocenylarenes was attempted in the presence of various catalytic systems: [RhCl(PPh3)3], [CoBr(PPh3)3], [NiBr2(dppe)]/Zn, [{Ir(cod)Cl}2]/dppe and [CpCo(cod)]/PPh3 [Cp = η5‐cyclopentadienyl, cod = η4‐cycloocta‐1,5‐diene, and dppe = 1,2‐bis(diphenylphosphanyl)ethane]. The results indicate that Wilkinson’s catalyst effects the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Co‐cyclotrimerization of ferrocenylalkynes 151 with α,ω‐diynes 98 to give functionalized ferrocenylarenes 152 has recently been studied under different catalyst conditions (Scheme ) 87. It was observed that Wilkinson’s catalyst afforded the ferrrocenylarenes in good yields and under mild conditions irrespective of the natures of the functional groups present.…”
Section: Partial Intramolecular [2+2+2] Cycloaddition: Co‐cyclotrimentioning
confidence: 99%
“…Co‐cyclotrimerization of ferrocenylalkynes 151 with α,ω‐diynes 98 to give functionalized ferrocenylarenes 152 has recently been studied under different catalyst conditions (Scheme ) 87. It was observed that Wilkinson’s catalyst afforded the ferrrocenylarenes in good yields and under mild conditions irrespective of the natures of the functional groups present.…”
Section: Partial Intramolecular [2+2+2] Cycloaddition: Co‐cyclotrimentioning
confidence: 99%
“…1 H NMR (400 MHz) and 13 C NMR (100 MHz) spectra (δ, ppm; J, Hz) were recorded on a Varian Unity Inova 400 spectrometer using tetramethylsilane as an internal standard. Infrared spectra (ν, cm -1 ) were recorded on a PE-640 Perkin-Elmer spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…One of the interesting substrates for such a venture are ethynylferrocenes owing to the bulkiness and redox activity of the ferrocene unit. Reports on the use of ethynylferrocenes in cyclotrimerization are still scarce 12 and only the recent study on their catalytic cocyclotrimerization with diynes showed their unique properties 13 . The aim of this work is to study the scope of the Ni-and Cu-catalyzed reactions between zirconacyclopentadienes and various ethynylferrocenes with respect to the alkyne substitution pattern.…”
mentioning
confidence: 99%
“…In particular, arylferrocenes are one of the most important structural motifs in these applications. Recently, the selective cyclocotrimerizations using 1,6-diynes and ferrocenylalkynes were achieved by Kotora, Štepni ∨ cka and co-workers as shown in Scheme 41 [63]. Recently, the selective cyclocotrimerizations using 1,6-diynes and ferrocenylalkynes were achieved by Kotora, Štepni ∨ cka and co-workers as shown in Scheme 41 [63].…”
Section: Iii-2 Synthesis Of Artificial Functional Moleculesmentioning
confidence: 99%
“…Recently, the selective cyclocotrimerizations using 1,6-diynes and ferrocenylalkynes were achieved by Kotora, Štepni ∨ cka and co-workers as shown in Scheme 41 [63]. The rhodium catalyst was also able to convert alcohol 124 to ferrocenylbenzyl alcohol 125 in moderate yield (Scheme 42) [63], while the regioselective synthesis of bis(ferrocenyl)isobenzofuran derivative 127 was achieved by means of the ruthenium-catalyzed cycloaddition of ferrocenyldiyne 126 with 122 (Scheme 43) [64]. For example, the malonatederived diyne 121 (X = C(CO 2 Et) 2 ) was allowed to react with 1 equiv of ethynylferrocene 122 for 24-48 h at 20 ˚C in the presence of 10 mol % catalyst to afford the desired ferrocenylindan 123 (X = C(CO 2 Et) 2 ) in 57 and 70% yields.…”
Section: Iii-2 Synthesis Of Artificial Functional Moleculesmentioning
confidence: 99%